Sirenomelia with vertebral, anal, cardiac defect, tracheo-esophageal fistula, renal anomalies, limb abnormalities association: a case report - Behera, Manas R.; Das, Swarnalata; Das, Palas (International Journal of Contemporary Pediatrics, 2020)
Sirenomelia is a rare congenital malformation, characterised by abnormal development of caudal part of body with variable degree of fusion of lower limbs. VACTERL is an acronym used for a group of sporadic non-random birth defects involving multiple organ systems, namely vertebral (V), anal (A), cardiac (C), tracheoesophageal (TE), renal (R) and limb (L) defects. Combination of both the anomalies is very rarely reported in literature. Survival is extremely rare and early prenatal diagnosis may allow for termination of pregnancy. Here we present a case of sirenomelia phenotype, with a complete spectrum of autopsy findings, suggestive of VACTERL association.